Parasitological, Haemato-biochemical and Immunological Responses in Garole Sheep Naturally Infected with Gastrointestinal Nematodes Dominant by Haemonchus contortus - Das, Supradip; Hembram, Ananta; Jas, Ruma; Brahma, Anupam; Kesh, Shyam Sundar; Bera, Santanu (International Journal of Bio-resource and Stress Management, 2025)
The experiment was conducted during June-August, 2023 at South Gurguria village and farms under the project ‘Biotech Kishan Hub’, Mohanpur, West Bengal to study gastrointestinal nematodes response in Garole sheep. Faecal samples from 70 Garole sheep aged 1-2 years of either sex were examined for three months (June-August, 2023) and total 210 animals were examined. In every month, based on FEC, 33 sheep were categorized in to 3 groups; non-infective (n=11; EPG=0), highly infective (n=11; EPG>500) and low infective (n=11; EPG<200) group and haematological, biochemical, immunological and clinical parameters were recorded in sheep of all the three groups. Uninfected sheep had significantly (p<0.01) higher values of haemoglobin (Hb) and packed cell volume (PCV) than both the low and highly infected groups, while peripheral eosinophil count (PEC) and total leukocyte count (TLC) were significantly higher in low infected group. Serum protein concentration including albumin and globulin levels, was significantly (p<0.01) reduced in both infected groups. Haemonchus contortus specific serum IgA concentration was significantly higher in the low infected group but, but serum IgG levels did not differ significantly between the groups. The body condition score (BCS) was found to be significantly (p<0.01) lower in the highly infected group than in the low infected group, which had significantly lower values compared to non-infected group. The results were exactly reversed in terms of FAMACHA score in the selected sheep. Gastrointestinal nematodes cause alterations in haematobiochemical profiles and also modulate immune response of the host; hence, these parasites should be managed properly.